PENGARUH MODEL PEMBELAJARAN TPS DENGAN MEDIA ICM TERHADAP HASIL BELAJAR KIMIA SISWA - rabiatul adawiyah; zona octarya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
AbstractThis research aimed at knowing the effect of using TPS learning model with ICM media toward student chemistry learning achievement on Hydrocarbon lesson at the tenth grade of State Senior High School 2 Rumbiojaya. It was instigated by the low of student chemistry learning achievement on Hydrocarbon lesson at the tenth grade of State Senior High School 2 Rumbiojaya. It was a Quasi-experiment with pretest and posttest design. Two classes of the tenth-grade students owning the same homogeneity level were the samples, the tenth grade of classes 2 was as the experimental group and class 3 was as the control group, and Purposive sampling technique was used. Observation, homogeneity test as the preliminary data test, pretest and posttest as the final data test, and documentation were the techniques of collecting the data. t test used to analyze the final data showed that tobserved was 2.038 and ttable was 2.00 at 5% significant level. It meant that tobserved was higher than ttable, H0 was rejected, and Ha was accepted. It revealed that there was an effect of using TPS learning model with ICM media toward student learning achievement on Hydrocarbon lesson and the coefficient of effect was 8.6%.Keywords : Think Pair Share, Index Card Match, Learning Achievement, Hydrocarbon.